Organized by Klitsa Antoniou - Antoniou, Klitsa (My University, 2026)
Homage to Jake & Dinos Chapman -- A Symposium for the Inauguration of the Fine Arts Program, at The Cyprus University of Technology. Keynote speakers: Jake Chapman, Dr. Sozita Goudouna, Dr. Efi Kyprianidou and Niki Young. Organizer